The Effect of Implementing the Card Sort Method on Fifth-Grade Students’ Science Learning Outcomes in Animal Classification - Sribanggai Sribanggai; Sri Marliah Puteri; Chairan Zibar L Parisu; Kasmawati Kasmawati (Journal of Education and Learning Sciences, 2025)
This study was motivated by the low science learning outcomes of elementary school students and the limited implementation of learning methods that actively engage students in the learning process, particularly in understanding conceptual material on animal classification. This study aimed to examine the effect of the Card Sort method on the science learning outcomes of fifth-grade students in animal classification material. A quantitative approach with a quasi-experimental method was employed using a Posttest-Only Nonequivalent Control Group Design. The sample was selected through total sampling and consisted of 56 students, including 29 students in Class VA as the experimental group, which received instruction using the Card Sort method, and 27 students in Class VC as the control group, which received instruction using the Make a Match model. Data were collected using a 20-item multiple-choice learning outcomes test. The instrument demonstrated good validity, with item correlation coefficients exceeding the r-table value of 0.367, and high reliability with a Cronbach’s Alpha coefficient of 0.889. Data analysis included descriptive statistics, normality and homogeneity tests, and an Independent Samples t-Test using IBM SPSS Statistics Version 27. The results showed that the experimental group achieved a higher mean score (81.38) than the control group (70.74). The data were normally distributed and homogeneous, with a Levene’s test significance value of 0.050. The Independent Samples t-Test yielded a significance value of 0.000 (p < 0.05), with a mean difference of 10.639. These findings indicate a significant difference in science learning outcomes between students taught using the Card Sort method and those taught using the Make a Match model. Therefore, the Card Sort method can be considered an effective active-learning strategy for improving elementary students’ understanding and learning outcomes in animal classification.